Production and characterization of chitosan/gelatin/β-TCP scaffolds for improved bone tissue regeneration - Serra, Inês Raquel Tavares (2018)
Recently, bone tissue engineering emerged as a viable therapeutic alternative, comprising bone implants and new personalized scaffolds to be used in bone replacement and regeneration. In this study, biocompatible scaffolds were produced by freeze-drying, using different formulations (chitosan, chitosan/gelatin, chitosan/β-TCP and chitosan/gelatin/β-TCP) to be used as temporary templates during bone tissue regeneration. Sample characterization was performed through attenuated total reflectance-Fourier transform infrared spectroscopy, X-ray diffraction and energy dispersive spectroscopy analysis. Mechanical characterization and porosity analysis were performed through uniaxial compression test and liquid displacement method, respectively. In vitro studies were also done to evaluate the biomineralization activity and the cytotoxic profile of the scaffolds. Scanning electron and confocal microscopy analysis were used to study cell adhesion and proliferation at the scaffold surface and within their structure. Moreover, the antibacterial activity of the scaffolds was also evaluated through the agar diffusion method. Overall, the results obtained revealed that the produced scaffolds are bioactive and biocompatible, allow cell internalization and show antimicrobial activity against Staphylococcus aureus. Such, make these 3D structures as potential candidates for being used on the bone tissue regeneration, since they promote cell adhesion and proliferation and also prevent biofilm development at their surfaces, which is usually the main cause of implant failure.